Comparative Evaluation of Human Mesenchymal Stem Cells of Fetal (Wharton's Jelly) and Adult (Adipose Tissue) Origin during Prolonged In Vitro Expansion: Considerations for Cytotherapy - I. Christodoulou; F. N. Kolisis; D. Papaevangeliou; V. Zoumpourlis (Stem Cells International)
Mesenchymal stem cells (MSCs) are somatic cells with a dual capacity for self-renewal and differentiation, and diverse therapeutic applicability, both experimentally and in the clinic. These cells can be isolated from various human tissues that may differ anatomically or developmentally with relative ease. Heterogeneity due to biological origin or in vitro manipulation is, nevertheless, considerable and may equate to differences in qualitative and quantitative characteristics which can prove crucial for successful therapeutic use. With this in mind, in the present study we have evaluated the proliferation kinetics and phenotypic characteristics of MSCs derived from two abundant sources, that is, fetal umbilical cord matrix (Wharton's jelly) and adult adipose tissue (termed WJSC and ADSC, resp.) during prolonged in vitro expansion, a process necessary for obtaining cell numbers sufficient for clinical application. Our results show that WJSC are derived with relatively high efficiency and bear a substantially increased proliferation capacity whilst largely sustaining the expression of typical immunophenotypic markers, whereas ADSC exhibit a reduced proliferation potential showing typical signs of senescence at an early stage. By combining kinetic with phenotypic data we identify culture thresholds up to which both cell types maintain their stem properties, and we discuss the practical implications of their differences.